Collaboration-Based Learning in the Era of the 4.0 Industrial Revolution - Imam Mujahid (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to describe collaboration-based learning in elementary schools. This type of research is qualitative research with a phenomenological approach. The speakers in this study were teachers and principals. Collecting data through observation, in-depth interviews, and documentation study. The validity of the data used was the triangulation of methods and sources. Data analysis in this study used data reduction, data presentation, and conclusion drawing. The results of the study show in 2 ways: 1). Collaborative learning where students do more learning through class discussions and completing assignments in groups. The implementation of this collaborative learning is carried out to create child-friendly schools that always involve students in real activities. teachers who teach learning in both high and low classes orientate their students to always communicate and interact in the teaching and learning process. 2). The implementation of the outing class is carried out programmatically by each class teacher to suit the theme being studied. This activity is carried out in places that have a value following the theme being studied for the achievement of student attitudes. This activity has been programmed in all classes with the scheduling system for each class.